Women's Participation in Selection of Contraceptive Methods – Knowledge, Attitudes and Culture in Formosa Public Health Center, Dili - Barreto Amaral, Meriana; de Jesus Maceiras, Maria; Guterres Correia, Avelino; Pires, Alexandra (Rifa'Institute, 2023)
Introduction: Family planning is a program that contributes to the improvement of women's health by reducing maternal mortality, abortion, freedom of choice and empowerment of women, reduction of subsequent female fertility, and is a program that aims to inform the people through a set of actions and attitudes (clinics and health practices) to guide as to contraception. Methods: This research uses a qualitative and quantitative approach, descriptive and field, held in Formosa Public Health Center, Dili. Results and Discussion: The result reveals that women in the age group with the highest expression in this research is 20 to 24 years old, hold an educational level with higher education about 30.5%. Emphasizing that more than half of the participants reported that they do not have information and only 13.7% getting information by personal health professionals. Regarding knowledge, most of participants did not obtain information regarding family planning and more less 51.5% had reasons to adhere to family planning is to prevent pregnancy. Factors that influencing the decision of the participants, mostly (94.0%) did not mention any factor as its decision. In terms of the type of use, 63.6% prefer the injectable method and almost 66.7% lamented some side effects such as dizziness and headaches and menstrual disorders, although they continue to use after consultation to a doctor or midwife. Conclusion: Finally, the duration of use about one-third of participants used about a year and 28.8% are new customers.